Influence Analysis Fundamentals on Stock Prices in the Company Bankings Listed on Stock Exchange Indonesia Period 2017-2021 - Hakim, Lukman; Susilowati, Dewi (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2023)
The purpose of this study is to confirm the effect of debt-to-equity (DER), price-to-earnings (PER) and return on equity (ROE) on service stock prices banks of companies registered on the Indonesian Stock Exchange for the period 2017 -2021. Population used in this study is the same as a sample of 6 companies that is company banking which registered in index Infobank 15 by consecutively during the period 2017-2021 with 30 financial statements. Sample determined with technique purposive sampling. The data used in this study are secondary data. The analytical method used is multiple linear regression. Research results show that the part of the debt-to-equity ratio (DER) has a negative effect and important for stock prices in the banking sector companies period 2017-2021. Price Earning ratio (PER) partially positive effect and significant to Price Share on company banking period 2017-2021. Return On Equity (ROE) by Partial take effect positive and significant to Price Share on company banking period 2017-2021. Debt-to-equity (DER), price-to-earnings (PER) and return on equity (ROE) simultaneously have a positive effect and significant to Price Share on company banking period 2017-2021.